Analysis and numerical correction of aberration in interferometric particle imaging. (July 2023) - Brunel, Marc; Abad, Alexis; Delestre, Barbara; Frodello, Quentin; Brunel, Rémi; Coëtmellec, Sébastien; Talbi, Mohamed
Highlights: We describe the role of spherical aberration in interferometric particle imaging. We propose a wave optics model to predict the interferometric images of rough particles in presence of this aberration. We propose a method to correct numerically the interferometric images affected by this aberration. Abstract: Interferometric Particle Imaging (IPI) is a convenient technique to determine the size and the shape of irregular rough particles. But it requires the analysis and the correction of all sources of noise that can modify the interferometric images and thus the reconstruction procedure. This study describes the role of spherical aberration in IPI. It proposes a numerical model to predict IPI images in presence of this aberration and a method to correct his effect.